Scaffolding Criticality: Iterations of Theory in Principal Preparation - Jo Beth Jimerson; Ron D. Myers (Education Sciences)
Theory can be of immense value in practice and to practitioners, but is sometimes perceived as esoteric and inaccessible, or divorced from “real-world” knowledge and skills needed to enact school leadership. Policy and scholarship also call for the development of school leaders capable of thinking in ways informed by a range of theories that help leaders consider issues from various perspectives. Developing principals capable of leading for the moment and in ways that improve PK–12 systems requires us to communicate about theory in a way that positions it as a window into and lens for practice and to make theory approachable for students. In this paper, drawing on scholarship and on our roles as principal preparation faculty and as former school principals, we outline a framework for thinking about and with theory in principal preparation and for embedding theory in learning in explicit ways. Together, the iterations of theory we discuss scaffold the ability of leaders to use theory to frame critical analyses, problem-solve, broaden awareness of educational and societal issues, and constructively critique K–12 education.